2015
DOI: 10.2217/bmm.15.26
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for CNS Involvement in Pediatric Lupus

Abstract: CNS disease, or central neuropsychiatric lupus erythematosus (cNPSLE), occurs frequently in pediatric lupus, leading to significant morbidity and poor long-term outcomes. Diagnosing cNPSLE is especially difficult in pediatrics; many current diagnostic tools are invasive and/or costly, and there are no current accepted screening mechanisms. The most complicated aspect of diagnosis is differentiating primary disease from other etiologies; research to discover new biomarkers is attempting to address this dilemma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 119 publications
(135 reference statements)
0
15
0
Order By: Relevance
“…32 Research is ongoing for reliable noninvasive biomarkers in this age group to determine whether anxiety and depression is specifically related to disease activity. 33 A systematic review by Quilter et al reported the prevalence of depressive symptoms in childhood onset SLE to be 6.7-59% and anxiety 34-37%. 13 In conditions such as SLE or other systemic vasculitides, as well as potential direct effects on the brain and nervous system caused by the condition itself, the impact of receiving a diagnosis such as these conditions and coming to terms with it, the relative rarity of the conditions, their potential severity, uncertainty of outcome and significant side effects of necessary drug therapy may all contribute to mental health in such young people.…”
Section: Sle and Vasculitidesmentioning
confidence: 99%
“…32 Research is ongoing for reliable noninvasive biomarkers in this age group to determine whether anxiety and depression is specifically related to disease activity. 33 A systematic review by Quilter et al reported the prevalence of depressive symptoms in childhood onset SLE to be 6.7-59% and anxiety 34-37%. 13 In conditions such as SLE or other systemic vasculitides, as well as potential direct effects on the brain and nervous system caused by the condition itself, the impact of receiving a diagnosis such as these conditions and coming to terms with it, the relative rarity of the conditions, their potential severity, uncertainty of outcome and significant side effects of necessary drug therapy may all contribute to mental health in such young people.…”
Section: Sle and Vasculitidesmentioning
confidence: 99%
“…In recent years, the availability of powerful tools to scan both the genome and proteome have revolutionized and greatly accelerated biomarker discovery. Pediatrician scientists have embraced these tools for the study of cSLE (29)(30)(31)(32)(33)(34).…”
Section: Advances In Identification Of Biomarkers For Nephritismentioning
confidence: 99%
“…MCP-1 (monocyte chemoattractant protein) urinary levels can also predict improvement of renal disease (31). Despite high sensitivity and responsivity to LN activity, MCP-1, RANTES, and TWEAK lack specificity for LN, and have also been found in cerebral spinal fluid and linked to the development of central neuropsychiatric involvement in cSLE (33). NGAL is also a biomarker for acute kidney injury and MCP is for chronic kidney disease in patients without SLE.…”
Section: Advances In Identification Of Biomarkers For Nephritismentioning
confidence: 99%
“…However, a meta-analysis of a large cohort of lupus patients demonstrated that antiribosomal P antibodies were not related to any diffuse manifestations and possessed limited diagnostic value for focal elements of NPSLE [60]. Interestingly, the prevalence of anti-ribosomal P antibody in pediatric lupus (20–42%) is twice as that of adult patients (10–20%), indicating that the sensitivity of this biomarker may be age dependent [61]. Overall, as in the case of anti-NMDAR antibodies, the exact role of anti-ribosomal P antibodies in NPSLE remains inconclusive.…”
Section: B Cells and Autoantibodies In Human Npslementioning
confidence: 99%
“…Interestingly, as is the case with anti-ribosomal P antibodies, anti-phospholipid antibodies are more prevalent in children with NPSLE compared to adults [61]. However, most of these studies fail to show a significant association between anti-β2 glycoprotein I antibodies and neuropsychiatric symptoms [62].…”
Section: B Cells and Autoantibodies In Human Npslementioning
confidence: 99%